Energy Economics and Policy in Developed Countries - Heshmati, Almas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This collected volume consists of high-quality research covering a wide range of topics related to energy economics and politics in developed countries. The papers are informative on how to encourage sustainable development and facilitate financing technology development, transfer, and applications to mitigate climate change. Air pollution, environmental regulations, green energy, energy certificates, transmission rights, and power generation are among the energy-related topic analyzed by the contributions included in this Special Issue.